Technological effort in developing countries: multinational corporations in Malaysia - Abd Halim Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2000)
This paper examines the factors that influence the likelihood of MNCs undertaking technological effort in developing countries, using a data set obtained from a survey. Factors such as modification to the main production line by MNCs and assistance they rendered to local firms were found significant in indicating the likelihood of technological activities. The paper also provides evidence that export-oriented MNCs in developing host countries do undertake technological effort for effective participation in the world market.